Sistemi di scarico articolare extra-capsulari del ginocchio: stato dell’arte - Zedde, P.; Uboldi, F.M.; Denti, F.; Puddu, L.; Cudoni, S. (Lo Scalpello - Journal, 2019)
EXTRA-CAPSULAR KNEE JOINT UNLOADING IMPLANT SYSTEM: STATE OF THE ARTThe treatment of early osteoarthritis of the knee can also be addressed with the use of different techniques that providefor the discharge of the affected joint compartment. Internal extra-articular devices consist of metal orpolycarbonate-urethane shock absorbers fixed to the femur and tibia by angular stability plates. Their purpose is tounload the joint and allow for reduction of the intra-articular compressive strength in the first degrees of flexionwithout modifying its anatomy and biomechanics and, therefore, being reversible. The literature is lacking inmedium- and long-term clinical results with the presence of limited case series or case reports with contrasting resultsthat do not provide significant conclusions on their efficacy but highlight some complications. Further studies areneeded, as the theory is very promising.